2014
DOI: 10.1098/rspb.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variation in influenza A virus prevalence and subtype diversity in migratory mallards in northern Europe

Abstract: Data on long-term circulation of pathogens in wildlife populations are seldom collected, and hence understanding of spatial-temporal variation in prevalence and genotypes is limited. Here, we analysed a long-term surveillance series on influenza A virus (IAV) in mallards collected at an important migratory stopover site from 2002 to 2010, and characterized seasonal dynamics in virus prevalence and subtype diversity. Prevalence dynamics were influenced by year, but retained a common pattern for all years whereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(216 citation statements)
references
References 47 publications
13
199
0
1
Order By: Relevance
“…The degree of host population immunity is an important driver of the diverse AIV antigenic subtypes that dominate regional sites from year to year (54). For example, antigenic drift likely results in the absence of similar HA gene lineages (i.e., AIV surface protein ¡ host immunity target) across migratory seasons at the regional sites observed in this study (55).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of host population immunity is an important driver of the diverse AIV antigenic subtypes that dominate regional sites from year to year (54). For example, antigenic drift likely results in the absence of similar HA gene lineages (i.e., AIV surface protein ¡ host immunity target) across migratory seasons at the regional sites observed in this study (55).…”
Section: Discussionmentioning
confidence: 99%
“…High effort longitudinal sampling of Mallards at a stopover site in Sweden has shown that the majority of the seasonal variation can be accounted for in epidemiological models (Latorre-Margalef et al, 2014). In Figure 2B, LPAIV prevalence over time is depicted at a stopover site in Sweden.…”
Section: Lpai Virus Dynamics In Mallardsmentioning
confidence: 99%
“…From longitudinal sampling of LPAIV in Mallards and other dabbling ducks conducted in Europe we know that virus prevalence follows a seasonal pattern, whereby the prevalence is low during the late winter, spring, and summer, followed by a peak in viral prevalence during the autumn migration (Ito et al, 1995;Hatchette et al, 2004;Olsen et al, 2006;Wilcox et al, 2011;Latorre-Margalef et al, 2014). This pattern has been observed at a number of study sites across the Northern Hemisphere, including Sweden (Latorre-Margalef et al, 2014), The Netherlands van Dijk et al, 2014) , Canada (Alberta, (Sharp et al, 1997;Hatchette et al, 2004)), USA (e.g.…”
Section: Lpai Virus Dynamics In Mallardsmentioning
confidence: 99%
“…Influenza A viruses can infect many species of warm-blooded vertebrates [26], but the great majority of viral strains appear to be found in wild waterbirds, such as shorebirds and gulls (Charadriiformes) and ducks and geese (Anseriformes) [12]. These species can come into contact with domestic poultry, which can pose a direct threat to the poultry industry, and also provide a conduit for potential transmission to humans.…”
Section: Introductionmentioning
confidence: 99%